Between national cinemas: reframing films from Malaysia, Indonesia, and Singapore - Maharam, Mohd Erman (2021)
This study provides a critical transnational examination of films from three culturally and historically interrelated nations in Southeast Asia: Malaysia, Indonesia, and Singapore. Films from these countries are often studied as national cinemas distinct from one another. However, this thesis argues for a theorisation of these cinemas through the concept of Nusantara which speaks to the geographical, social, and cultural patterns of the region before the advent of film and nationalism in Southeast Asia. The overlapping cultural significance of the cinematic representations of these countries is analysed through themes of cultural identity, mobility and belonging. “Nusantara cinema” (or archipelagic cinema) is used as a strategy to evade national political boundaries, thus providing a critical look at transnationalism in film studies (Higbee & Lim, 2010) endeavouring to illustrate such links through motifs that speak to the region’s archipelagic culture of mobility, specifically the concept of tanahair (literally, ‘land and water’ meaning ‘homeland’) and merantau (to sojourn), as well as the treatment of borderland populations and cultural cosmopolitanism. Nusantara, a portmanteau for ‘between islands’ is a Malay word referring to island Southeast Asia. Drawing on Homi Bhabha’s theories of in-betweenness, hybridity and liminality, I argue that cultural representation in films from the three countries transcends the ethnonationalist frameworks of national culture and national cinema. Firstly, nusantara is a place where cultures meet and regularly compete in asymmetric power relations among groups and individuals who continually seek a feeling of belonging; it is not just their home, but also a ‘contact zone’ (Pratt, 2002). However, the multifaceted nature of merantau offers a rather complicated sense of place and homeland. Furthermore, the path of sojourners in films reacted to the political and cultural negotiations in the 1960s, 1970s and late 1990s. Currently, films from these countries highlight the borderland communities in liminality, thereby giving credence to transnational cultural identities, as well as promoting cultural and spatial connections across countries and linking Southeast Asia’s diversity.